Genetic diversity, sexual condition, and microhabitat preference determine mating patterns in Sphagnum (Sphagnaceae) peat‐mosses. (3rd March 2015) - Johnson, Matthew G.; Shaw, A. Jonathan
<x xml:space="preserve">Abstract</x> In bryophytes, the possibility of intragametophytic selfing creates complex mating patterns that are not possible in seed plants, although relatively little is known about patterns of inbreeding in natural populations. In the peat‐moss genus Sphagnum, taxa are generally bisexual (gametophytes produce both sperm and egg) or unisexual (gametes produced by separate male and female plants). We sampled populations of 14 species, aiming to assess inbreeding variation and inbreeding depression in sporophytes, and to evaluate correlations between sexual expression, mating systems, and microhabitat preferences. We sampled maternal gametophytes and their attached sporophytes at 12–19 microsatellite loci. Bisexual species exhibited higher levels of inbreeding than unisexual species but did generally engage in some outcrossing. Inbreeding depression did not appear to be common in either unisexual or bisexual species. Genetic diversity was higher in populations of unisexual species compared to populations of bisexual species. We found a significant association between species microhabitat preference and population genetic diversity: species preferring hummocks (high above water table) had populations with lower diversity than species inhabiting hollows (at the water table). We also found a significant interaction between sexual condition, microhabitat preference, and inbreeding coefficients, suggesting a vital role for species ecology in determining mating patterns in Sphagnum populations. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 115, 96–113.